The Concept of Inclusion in the Context of Sustainable Development - Salamucha, Agnieszka (Problemy Ekorozwoju, 2021)
The article presents a semantic analysis of the concept of inclusion, which – treated as the central category for Goal 16 of the 2030 Agenda for Sustainable Development (United Nations) – requires further definition. Initially, I outline the history and etymology of the word inclusion, provide various contexts of its use in Polish common language and in the academic area, take a closer look at the word family as well as synonyms and antonyms of the term inclusion (especially exclusion). Next, I explore functions of the concept of inclusion (descriptive, explanatory, normative) and problems regarding the concept. The conclusion contains four types of referents of the term inclusion.